Communicating carabids: Engaging farmers to encourage uptake of integrated pest management. Issue 6 (7th April 2022) - Jowett, Kelly; Milne, Alice E; Potts, Simon G; Senapathi, Deepa; Storkey, Jonathan
Abstract: BACKGROUND: Natural enemy pest control is becoming more desirable as restrictions increase on pesticide use. Carabid beetles are proven agents of natural‐enemy pest control (NPC), controlling pests and weeds in crop areas. Agro‐ecological measures can be effective for boosting carabid abundance and associated NPC, but the benefits of specific interventions to production are seldom communicated to farmers. We explore pathways to improved NPC by engaging farmers and increasing knowledge about farm management practices (FMPs) beneficial to carabids using engagement materials. We used a questionnaire to measure awareness, beliefs and attitudes to carabids and analysed these within a framework of the Theory of Planned Behaviour (TPB), relative to a control group. RESULTS: We found awareness of carabid predation to be associated with beliefs of pest and weed control efficacy. Within the framework of TPB, we found that current implementation of FMPs was higher if farmers perceived them to be both important for carabids and easy to implement. This was also true for future intention to implement, yet the perceived importance was influenced by engagement materials. Field margins/buffer strips and beetle banks (16% and 13% of responses) were the most favoured by farmers as interventions for carabids. CONCLUSION: The TPB is a valuable tool with which to examine internal elements of farmer behaviour. In this study self‐selected participants were influenced by online engagement in a single intervention, proving this approach has the potential to change behaviour. Our results are evidence for the effectiveness of raising awareness of NPC to change attitudes and increase uptake of sustainable practices. Abstract : Engagement interventions affected behavioural intentions of farmer participants primarily through altering beliefs about carabid pest control, resulting in more positive attitudes towards specific farm management practices. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.